Implementasi Permohonan Langsung Masyarakat Melalui Kantor Jasa Surveyor Berlisensi (KJSB) Di Kantor Pertanahan Kabupaten Gianyar - I Wayan Aldy Wira Sanjaya; Lis Julianti (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
Land registration activities are not only carried out by the scope of employees of the Ministry of ATR/BPN. The Licensed Surveyor Services Office (KJSB) is a business entity that has received a work permit from the Minister of ATR/BPN to provide its services in the land sector. Direct applications from the public (PLM) are services provided by KJSB to the public to register land. In the Gianyar Regency area, the Gianyar Regency Land Office has the authority to verify and validate PLM services submitted by KJSB. This study aims to determine the implementation and what factors influence the implementation of PLM through KJSB at the Gianyar Regency Land Office. The research method used is empirical legal research by conducting direct interviews with the Head of the Survey and Mapping Section and the Head of KJSB. The results of this study regarding the implementation of PLM through KJSB at the Gianyar Regency Land Office are implemented through 5 (five) stages and there are success factors, inhibiting factors and harmony strategies in the implementation of PLM through KJSB at the Gianyar Regency Land Office.